Toward High-Resolution Vertical Measurements of Dissolved Greenhouse Gases (Nitrous Oxide and Methane) and Nutrients in the Eastern South Pacific - Troncoso, Macarena; Garcia, Gerardo; Verdugo, Josefa; Farías, Laura (Frontiers in Marine Science, 2018)
In this study, in situ, real-time and high-resolution vertical measurements of dissolved greenhouse gases (GHGs) such as nitrous oxide (N2O) and methane (CH4) and nutrients are reported for the eastern South Pacific (ESP); a region with marked zonal gradients, ranging from highly productive and suboxic conditions in coastal upwelling systems to oligotrophic and oxygenated conditions in the subtropical gyre. Four high-resolution vertical profiles for gases (N2O and CH4) and nutrients (NO3- and PO43-) were measured using a Pumped Profiling System (PPS), connected with a liquid degassing membrane coupled with Cavity Ring-Down Spectroscopy (CRDS) and a nutrient auto-analyzer, respectively. The membrane-CRDS system maintains a linear response over a wide range of gas concentrations, detecting N2O and CH4 levels as low as 0.0774±0.0004 and 0.1011±0.001 ppm, respectively. Continuous profiles for gases and nutrients were similar to those reported throughout the ESP, with pronounced N2O and CH4 peaks at the upper oxycline and at the base of the euphotic zone and pycnocline, respectively, in the coastal zone; but almost constant depth profiles in the subtropical gyre. Additionally, other vertical gas and nutrient structures were observed using continuous sampling, which would not have been detected by discrete sampling. Our results demonstrate that continuous measurements can be a potentially useful methodology for future GHGs cycle studies.